CONCEPTUAL FRAMEWORK IN THE FIELD OF CORPORATE SECURITY: CONCEPTUAL FRAMEWORK IN THE FIELD OF CORPORATE SECURITY - Georgieva, Desislava (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
Corporate security is a dynamic and comprehensive concept crucial for the protection and stable functioning of business entities, involving measures against both internal and external threats. It is integral to national security, with corporate security subsystems addressing economic, informational, and social components. Effective corporate security requires the collaboration of various internal services and sometimes external agencies, adapting preventive and responsive strategies to safeguard vital interests and ensure sustainable development.